Comprehensive assessment of heavy metal pollution in northeast Fuqing Bay: integrating sediments, seawater, and marine organisms analysis with multivariate techniques - Enkang Wang; Yongchao Yang; Yonggen Sun; Jing Wang; Xuanbo Chen; Jiaojiao Yang; Jianqiang Wang; Chao Dong; Jiandong Qiu; Zhao Wang (Frontiers in Marine Science, 2025)
Northeastern Fuqing Bay is crucial for the marine ecosystem in Fujian Province and plays an important role in regional economic development and ecological balance. However, rapid economic and population growth has led to severe heavy metal (HM) pollution from anthropogenic sources and atmospheric deposition. This study comprehensively assessed HMs in surface sediments, surface seawater, and marine organisms in northeastern Fuqing Bay, Fujian Province. A total of 37 surface seawater samples, 22 surface sediment samples, and 4 marine organism samples were collected. The results indicated that certain HMs, such as Hg and Cd, exhibited high coefficients of variation in surface sediments. The concentrations of HMs in both surface seawater and sediments met Class I standards; however, some sediment samples were contaminated with Cd, As, and Hg, and the Cr levels in marine organisms exceeded the permissible limits at certain sampling sites. Analysis of various indices revealed that the mean potential ecological risk index ( RI ) value was 193.12, indicating moderate ecological risk, primarily influenced by Cd and Hg, whereas seawater was classified as having a low ecological risk, with mean RI value of 13.52. Marine organisms demonstrated a strong bioaccumulation capacity for certain HMs in seawater. Principal component analysis indicated that HM sources in sediments were mainly wastewater discharge from chemical enterprises, port operations, rock weathering, metal smelting, and agricultural activities. In contrast, HM sources in seawater were partly natural and partly related to anthropogenic activities, such as urban and rural sewage discharge. This study provides an important reference for the ecological restoration of this region.